(untitled) (Bangladesh Journal of Agriculture, 2022)
The experiment was designed to enhance seed germination and seedlings’ growth of chebulic myrobalan (Terminalia chebula Retz.) by proper seed soaking and sowing time after collection of fruits during March to July 2020 at BAU-GPC of Bangladesh Agricultural University, Mymensingh. In total 900 seeds were subjected to five pre-sowing treatments e.g. control or without soaking of seeds (C1), soaking in water for two days (C2), four days (C3), six days (C4), and soaking cow dung slurry for six days (C5) and four sowing times: on collection date and after 10, 20 and 30 days of collection respectively. The field experiment was conducted following RCBD with three replications. Seeds soaked in cow dung slurry (C5) showed the highest germination percentage (85.25%), germination energy (43.41%) and survival percentage (85.65%). Seeds sowing after 10 days of collection (P2) recorded as the highest germination percentage (81.37%) and germination energy (39.60%) whereas the highest survival percentage was observed after 30 days of collection (P4) (76.71%). After 30 days of collection, seeds soaked in cow dung slurry for six days (C5P4) showed highest germination (93%), survival percentage (92.86%), leaf number (60) and shoot length (32cm). The lowest germination percentage (60%) and leaf number (32.50) was observed in the treatment C1P4 and the lowest survival percentage (40%) and shoot height (12 cm) in C1P1. Bangladesh J. Agri. 2019-2021, 44-46: 45-54